2015
DOI: 10.1007/s00795-015-0125-0
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of membrane skeletal molecules in the Schmidt–Lanterman incisure in Schwann cells

Abstract: Membrane skeletal networks form a two-dimensional lattice structure beneath erythrocyte membranes. 4.1R-MPP (membrane palmitoylated protein) 1-glycophorin C is one of the basic molecular complexes of the membrane skeleton. An analogous molecular complex, 4.1G-MPP6-cell adhesion molecule 4 (CADM4), is incorporated into the Schmidt-Lanterman incisure (SLI), a truncated cone shape in the myelin internode that is a specific feature of myelinated nerve fibers formed in Schwann cells in the peripheral nervous system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
2
5
0
Order By: Relevance
“…Tseng et al observed that MPP6 might be involved in the assembly of Lin-7 protein complexes in epithelial and neuronal cells. Indeed, further studies confirmed that MPP6 and Lin-7 form, as already mentioned, a molecular complex with CADM4 and 4.1G in mouse peripheral neurons [84,[99][100][101][102]. In MPP6-deficient mice, Lin-7 expression was downregulated and absent in SLIs in Schwann cells, thus indicating MPP6 as a regulator of Lin-7 expression and localization.…”
Section: Mpps In Complexes Withsupporting
confidence: 70%
See 1 more Smart Citation
“…Tseng et al observed that MPP6 might be involved in the assembly of Lin-7 protein complexes in epithelial and neuronal cells. Indeed, further studies confirmed that MPP6 and Lin-7 form, as already mentioned, a molecular complex with CADM4 and 4.1G in mouse peripheral neurons [84,[99][100][101][102]. In MPP6-deficient mice, Lin-7 expression was downregulated and absent in SLIs in Schwann cells, thus indicating MPP6 as a regulator of Lin-7 expression and localization.…”
Section: Mpps In Complexes Withsupporting
confidence: 70%
“…An example of a protein complex, similar to those previously described, was discovered in mouse sciatic nerves, where MPP6 was found in the complex with protein 4.1G, Lin-7 (a MAGUK protein, which is described below in more detail) and another member of the Necl family (CADM4) [84,[99][100][101][102]. Immunostaining studies of MPP6 and CADM4 showed that, analogously to 4.1G, they can be found at the cell membrane of Schmidt-Lanterman incisures (SLIs) and paranodes [84,99].…”
Section: Mpps In Complexes With Ferm Family Memberssupporting
confidence: 54%
“…The differences between PNS myelin proteomes of Fa2h +/+ and Fa2h −/− mice were small in all age groups examined, and upon focusing on well-established myelin proteins, we observed a rather specific increase of the four proteins Cadm4, Mpp6 (Pals2), Lin7, and band 4.1G (Epb41l2). These four molecules are co-regulated at the protein and mRNA level [ 29 ], and there is clear evidence that they form a complex in SLIs [ 32 , 36 38 ]. Localization of this complex in SLIs depends on band 4.1G protein [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Terada's group has been studying the role of membrane protein complexes in the formation of myelin sheaths in mouse peripheral nervous system (Terada et al 2016;Saitoh et al 2017). In a recent publication (Saitoh et al 2017) using 4.1G-deficient mice, these authors demonstrated that the 4.1G protein component of the skeletal molecular complex 4.1G-membrane palmitoylated protein 6 (MMP6)-Lin7-cell adhesion molecule 4 (CADM4) functions as a signaling molecule for the proper formation of Schwann cell-associated myelin.…”
Section: Membrane Protein Factors Regulating Myelin Formationmentioning
confidence: 99%